8th International Conference on Web-based Learning - ICWLâ??09 - for Papers, Call (International Journal of Advanced Corporate Learning (iJAC), 2008)
ICWL is an annual international conference on web-based learning. Since the first ICWL was held in Hong Kong in 2002, it has been held in Australia (2003), China (2004), Hong Kong (2005), Malaysia (2006), United Kingdom (2007), and China (2008). The 8th ICWL 2009 will be held in Aachen, Germany, a city with rich culture, high-tech research, and a truly European spirit. ICWL 2009 will be jointly organized by Hong Kong Web Society, RWTH Aachen University, and Max-Planck-Institute for Computer Science. The technical program will feature keynote addresses, workshops, tutorials, in addition to presentations of refereed papers.